(untitled) (Journal of Renal and Hepatic Disorders, 2022)
COVID-19 pneumonia and community-acquired pneumonia (CAP) have been associated with morbidity and mortality. The aim of this study was to evaluate the outcome of hospitalized patients with COVID-19 pneumonia versus CAP in terms of mortality. This was a retrospective cohort study conducted between pre-COVID-19 era (May 2019–November 2019) and COVID-19 era (May 2020–November 2020). The study included all adult patients with COVID-19 pneumonia (Group 1) and adult patients with CAP but are COVID-19 negative (Group 2). A total of 106 patients were included in the study, of which 56 were in the COVID-19 pneumonia group and 50 in the CAP group. Patients who developed acute kidney injury (AKI) were 60.7% (n = 34) in Group 1 and 48% (n = 24) in Group 2. Mortality occurred in 37.5% (n = 21) patients in Group 1 and 12.0% (n = 6) in Group 2 (P = 0.003). A total of 52 patients required admission to intensive care unit (ICU), of which 44.6% (n = 25) were in Group 1 and 54.0% (n = 27) in Group 2. Of the 58 patients who developed AKI, 3 (8.8%) patients in Group 1 passed away compared to none in Group 2. Moreover, 58.8% patients (n = 20) in Group 1 and 70.8% patients (n = 17) in Group 2 required ICU admission. Mortality rate in the ICU was 80.0% (n = 16) and 35.3% (n = 6) in Groups 1 and 2, respectively (P = 0.006). The overall mortality rate was higher in case of COVID-19 patients than those with CAP. In case of patients with AKI, mortality rate in the ICU was significantly higher in COVID-19 pneumonia patients compared to CAP patients.